Estonia : Statistical Appendix. (IMF Staff Country Reports; Country Report, 2000)
The paper presents statistical data on gross domestic product, prices, average monthly wage, employment by sector, labor market indicators, unit labor costs by sector, summary of general government operations, general government revenue, and expenditures of Estonia. The paper also presents data on fiscal balances by government sector, analytical accounts of banking institutions, maturity and currency composition of deposits, average interest rates of deposits and loans, nonperforming loans of commercial banks, balance of payments, direction of trade-exports by countries, and other related economic indices.